1983
DOI: 10.1111/j.1476-5381.1983.tb10068.x
|View full text |Cite
|
Sign up to set email alerts
|

Barbiturates increase the rate of voltage‐dependent inactivation of the calcium current in snail neurones

Abstract: Effects of barbiturates (thiopentone, pentobarbitone, phenobarbitone and barbitone) on the calcium current (ICa) in identified Helix neurones were studied, using a conventional suction pipette technique. Barbiturates depressed the maximal peak amplitudes (MPA) of ICa in a dose‐dependent manner without shifting the current‐voltage relationships along the voltage axis. Barbiturates accelerated the decay phase of ICa at high concentrations (1 × 10−4 to 3 × 10−3 m), at which concentrations double‐pulse experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It has been suggested that the sodium and calcium currents underlying the spikes are equally sensitive to pentobarbital ( Goldring and Blaustein, 1982 ) in the giant R2 neuron of Aplysia. Thiopentone, pentobarbitone, phenobarbitone and barbitone, all accelerated the decay phase of the I Ca in Helix aspersa neurons ( Nishi and Oyama, 1983a ), and pentobarbitone also inhibited its maximum peak amplitude ( Nishi and Oyama, 1983b ). In Aplysia neurons in excised ganglia, both pentobarbital and phenobarbital enhanced spike frequency adaptation via a slowly developing outward current unique to neurons of this type ( Cote et al, 1978 ; Zbicz and Wilson, 1981 ) and in other neurons they depressed chloride-dependent inhibitory responses to either iontophoretically applied acetylcholine or GABA ( Cote and Wilson, 1980 ) and attenuated excitatory responses while potassium-dependent inhibitory responses were minimally affected.…”
Section: Actions Of Clinical Anesthetics On Gastropod Molluscsmentioning
confidence: 99%
“…It has been suggested that the sodium and calcium currents underlying the spikes are equally sensitive to pentobarbital ( Goldring and Blaustein, 1982 ) in the giant R2 neuron of Aplysia. Thiopentone, pentobarbitone, phenobarbitone and barbitone, all accelerated the decay phase of the I Ca in Helix aspersa neurons ( Nishi and Oyama, 1983a ), and pentobarbitone also inhibited its maximum peak amplitude ( Nishi and Oyama, 1983b ). In Aplysia neurons in excised ganglia, both pentobarbital and phenobarbital enhanced spike frequency adaptation via a slowly developing outward current unique to neurons of this type ( Cote et al, 1978 ; Zbicz and Wilson, 1981 ) and in other neurons they depressed chloride-dependent inhibitory responses to either iontophoretically applied acetylcholine or GABA ( Cote and Wilson, 1980 ) and attenuated excitatory responses while potassium-dependent inhibitory responses were minimally affected.…”
Section: Actions Of Clinical Anesthetics On Gastropod Molluscsmentioning
confidence: 99%